Agency in Community: Understanding Gender-Based Violence from within a Muslim Community in Lenasia, Johannesburg - Aaishah Lombard; Elina Hankela (Journal for the Study of Religion)
This qualitative study examines how a group of Muslims in a conservative community in Lenasia, Johannesburg, engaged with Islam and gender-based violence (GBV). Drawing on the framework of lived religion and Saba Mahmood’s conceptualization of agency and embodiment, the article highlights how the 13 interviewees actively negotiated their perceptions of and approach to GBV within their religious and cultural environment. First, the participants actively chose their religious authorities and illustrated how these authorities portrayed an Islam that is gender-just. Second, while largely opting to rather ignore than criticize probable patriarchal tones in their religion, participants freely expressed their critical views on patriarchy and GBV in relation to their culture. Through highlighting the agency and logic in the participants’ engagement with GBV, the article underscores the importance of involving conservative religious communities in combating GBV in their own terms.